Cover Picture. Issue 1 (12th March 2021) - Unknown
Abstract : This cover image is based on the original article SARS‐CoV‐2 infection aggravates chronic comorbidities of cardiovascular and diabetic diseases in mice by Yuanwu Ma et al. DOI: ‐ 10.1002/ame2.12155 . Cardiovascular diseases (CVDs) and diabetes mellitus (DM) are top two chronic comorbidities that increase the severity and mortality of COVID‐19. This article took advantage of adenovirus to deliver h‐ACE2 to lung to enable SARS‐CoV‐2 infection in mice, and studied SARS‐CoV‐2's impacts on pathogenesis of chronic diseases. In this study, mouse models mimicked the complex pathological symptoms of COVID‐19 patients with chronic diseases were established. This work provided valuable information to better understand the interplay between the primary diseases and SARS‐CoV‐2 infection.